Lipid oxidation inhibition through active polylactic acid films with rosemary and green tea extracts - Andrade, Mariana (2022)
More and more, consumers are demanding natural products with longer shelf-life. Extracts from rosemary (Rosmarinus officinalis L.) and green tea (Camellia sinensis L.) have high antimicrobial and antioxidant activities. These extracts can be incorporated into polymers produced from renewable sources, to produce active biopackaging. This concept intends to positively interact with packaged food, to inhibit the natural degradation of food, maintaining the quality of the packaged food and increasing its shelf-life. The antioxidant activity of food grade extracts from rosemary and green tea was evaluated and the total content in phenolic compounds and flavonoids was determined.